2015
DOI: 10.3390/ijms160921975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Dendrobium Species (Orchidaceae) Based on the DNA Barcode ITS2 Region and Its Application for Phylogenetic Study

Abstract: The over-collection and habitat destruction of natural Dendrobium populations for their commercial medicinal value has led to these plants being under severe threat of extinction. In addition, many Dendrobium plants are similarly shaped and easily confused during the absence of flowering stages. In the present study, we examined the application of the ITS2 region in barcoding and phylogenetic analyses of Dendrobium species (Orchidaceae). For barcoding, ITS2 regions of 43 samples in Dendrobium were amplified. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 54 publications
6
63
0
5
Order By: Relevance
“…Chrysotoxae formed two clades (1, 2), which indicated that sect. Chrysotoxae was probably polyphyletic, and this result was consistent with precious reports (Feng et al, 2015b). It was reported that sect.…”
Section: Figsupporting
confidence: 82%
See 2 more Smart Citations
“…Chrysotoxae formed two clades (1, 2), which indicated that sect. Chrysotoxae was probably polyphyletic, and this result was consistent with precious reports (Feng et al, 2015b). It was reported that sect.…”
Section: Figsupporting
confidence: 82%
“…Thus, it is necessary to exploit other barcode loci as supplementary molecular marker to distinguish these species. Due to their vegetative similarity, abundant species and lapped morphologic variation within some species (Xu et al, 2015), Dendrobium taxonomy is considered as the most complicated challenges in Orchidaceae (Feng et al, 2015b). As the findings of other molecular researches, this study also found that infrageneric taxa of Dendrobium were not monophyletic (Xiang et al, 2013;Feng et al, 2015a, b).…”
Section: Figsupporting
confidence: 55%
See 1 more Smart Citation
“…Numerous studies have focused on searching the most appropriate DNA loci for low taxonomic level studies of Dendrobium species 5, 6, 16 . However, due to limited loci or taxes sampled, some conclusions made in these studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal DNA barcode could provide significant species discrimination and identification (Feng et al, 2014; Gong et al, 2016; Nigro et al, 2016). We used two different analyses to evaluate the discrimination rates between species and sections within Aceraceae.…”
Section: Discussionmentioning
confidence: 99%